PARTICLE SIZE DISTRIBUTION OF NANOSCALE ULEXITE MINERAL PREPARED BY BALL MILLING - Kutuk, Sezai; Kutuk Sert, Tuba (MATTER: International Journal of Science and Technology, 2017)
Commercially available raw ulexite (U) minerals were milled up to 120 min by using a high-energy ball grinder for different initial feed sizes (−75 µm and −3 mm), ball to powder ratios (5:1 and 10:1), ball sizes (1 mm and 5 mm), and process control agents (3% and 6%). Particle size distribution and morphology measurements of milled powders were carefully studied. In particle size analysis, the lowest d90, d50, d10 and dmin values were detected to be 17.547 µm, 1.732 µm, 283 nm and 35 nm, respectively. Therefore, nanoscale in particle size for the ulexite mineral has been achieved. In addition, the smallest milling time was found as 30 min. Moreover, the best powder yield was determined to be 90.5%. In morphology analysis, the milled powders were observed to be more homogeneous than the initial feed size minerals. Besides, findings of morphology analysis were in agreement with that of particle size analysis. It was decided that optimized ball milling parameters are −3 mm for initial feed size; 10:1 for the ball to powder ratio; 5 mm for ball size; 3% for process control agent. The results obtained from this work will be useful for nanoscale research and industrial applications of ulexite (Na2O.2CaO.5B2O3.16H2O) material, which is boron mineral.